Utvärdering av Di35M-PrLO-projektion av armbågsleden för utlinjering av mediala processus coronoideus hos hund - Kihlström, Jerker (2008)
The aim of this study is to evaluate an alternative projection of the Medial Coronoid Process (MCP) of the canine elbow joint. The projection (Di35M-PrLO) was, to my knowledge, first mentioned in an article by Haudiquet et al in 2002. In that article the projection was tested in vitro, and a good sensitivity was showed for the Medial Coronoid Process. The projection might be helpful in cases of suspected Fragmented Coronoid Process (FCP) . This study is divided into three parts. The first part is an in-vivo test of the projection, including technique and subjective evaluation of the outlining of the MCP. Part two is an in-vitro study of different positioning of the humerus in the Di35M-PrLO, in order to see which part of the MCP is best outlined in which position. Part three is an evaluation of the positioning technique, in order to see if the projection is usable in standard clinical situations.